Malignant Peripheral Nerve Sheath Tumour of the Maxilla - Puja Sahai; Bidhu Kalyan Mohanti; Devajit Nath; Suman Bhasker; Subhash Chander; Sameer Bakhshi; Chirom Amit Singh (Case Reports in Otolaryngology)
A 38-year-old man was diagnosed with malignant peripheral nerve sheath tumour of the maxilla. He was treated with total maxillectomy. Histopathological examination of the resected specimen revealed a close resection margin. The tumour was of high grade with an MIB-1 labelling index of almost 60%. At six weeks following the surgery, he developed local tumour relapse. The patient succumbed to the disease at five months from the time of diagnosis. The present report underlines the locally aggressive nature of malignant peripheral nerve sheath tumour of the maxilla which necessitates an early therapeutic intervention. A complete resection with clear margins is the most important prognostic factor for malignant peripheral nerve sheath tumour in the head and neck region. Adjuvant radiotherapy may be considered to improve the local control. Future research may demarcate the role of targeted therapy for patients with malignant peripheral nerve sheath tumour.